Teacher education - Panda, Bhujendra Nath; Tewari, A. D., 1957- (A.P.H. Publishing Corporation, 1997)
Contributed papers of the 29th Annual Conference of the Indian Association of Teacher Educators, was organized from 23-25 December 1995, at Regional Institute of Education, Bhubaneswar.